2016
DOI: 10.1186/s12870-016-0824-2
|View full text |Cite
|
Sign up to set email alerts
|

Interdependency of Reactive Oxygen Species generating and scavenging system in salt sensitive and salt tolerant cultivars of rice

Abstract: BackgroundSalinity stress is a major constrain in the global rice production and hence serious efforts are being undertaken towards deciphering its remedial strategies. The comparative analysis of differential response of salt sensitive and salt tolerant lines is a judicious approach to obtain essential clues towards understanding the acquisition of salinity tolerance in rice plants. However, adaptation to salt stress is a fairly complex process and operates through different mechanisms. Among various mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 41 publications
7
80
0
Order By: Relevance
“…The increase of ROS accumulation and MDA content alter superoxide dismutase (SOD) activity and catalase (CAT) activity, and damage photosynthesis and cell structure under stress conditions [45,46]. Moreover, a previous study suggested that the activated enzymatic antioxidant system contributed to ROS scavenging and inhibition of lipid peroxidation [47,48]. This study showed that POD and SOD activity increased at 48 h after TDZ treatment; however, CAT activity decrease.…”
Section: Ros Homeostasis In Leaf Abscission In Respond To Tdzmentioning
confidence: 65%
“…The increase of ROS accumulation and MDA content alter superoxide dismutase (SOD) activity and catalase (CAT) activity, and damage photosynthesis and cell structure under stress conditions [45,46]. Moreover, a previous study suggested that the activated enzymatic antioxidant system contributed to ROS scavenging and inhibition of lipid peroxidation [47,48]. This study showed that POD and SOD activity increased at 48 h after TDZ treatment; however, CAT activity decrease.…”
Section: Ros Homeostasis In Leaf Abscission In Respond To Tdzmentioning
confidence: 65%
“…The SODs catalyze the conversion of O • 2 À into H 2 O 2 , which acts as a signal molecule to trigger resistance to various biotic and abiotic stresses (Quan et al, 2008;Kaur et al, 2016;Saxena et al, 2016). However, the excess H 2 O 2 results in the occurrence of oxidative stress and leads to programmed cell death (PCD), Fig.…”
Section: Researchmentioning
confidence: 99%
“…Therefore, SODs act as key defense factors against versatile stresses by regulating the H 2 O 2 concentration in plants. H 2 O 2 is a vital ROS in biological processes leading to tolerance against various stresses (Kaur et al, 2016;Saxena et al, 2016).Consistent with the role of ROS in rice immunity, the resistant rice cultivar IRBLKm-Ts displays higher H 2 O 2 concentrations than the susceptible cultivar Lijiang XinTuan Hegu (LTH) upon M. oryzae infection (Li et al, 2014). In addition, overexpression of L-ascorbate oxidase (AO) enhanced AO-mediated H 2 O 2 accumulation, thereby improving resistance to rice stripe virus (Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors play an essential role in rice development and responses to biotic and abiotic stresses [36][37][38][39]; these five TFs have been reported to respond to salt stress in rice to varying degrees [40,41]. The reactive oxygen species signaling pathway mediated by peroxidase was also critical, as it evoked a cascade of responses related to stress tolerance [42][43][44]. The aggregation of related genes in the same chromosome region might be a key feature underlying the salt tolerance of SR86.…”
Section: Discussionmentioning
confidence: 99%